Legal Protection for Heirs Against the Transfer of Land Ownership Rights Through Underhand Sales and Purchase Agreements Without the knowledge of the heirs (Study Decision Number 41/PDT.G/2020/PN CELL) - Agus Antoni, Mochamad; Rahmatiar, Yuniar; Abas, Muhamad (Journal of Law, Politic and Humanities, 2024)
Referring to Law no. 5 of 1960 concerning Basic Agrarian Principles (UUPA), registration of land rights and the transfer of rights are regulated in Article 19 of the UUPA and its implementing regulations. A land certificate is official evidence that shows ownership status or rights to land. When the name of the land owner is on the land certificate or land deed registered by PPAT changes from seller to buyer, this is referred to as a transfer of property rights . However , it is still common for transfers of land rights to be carried out independently / privately without involving the authorities or without following established procedures . This can lead to legal uncertainty and potential problems regarding land ownership in the future. Normative juridical methods are used as the basis for research, descriptive analytical methods are the specifications in this research . Results: 1) Preventive legal protection and repressive legal protection are legal protection that can be provided in private land sale and purchase transactions . 2) Based on Articles 1451 and 1452 of the Civil Code, the Panel of Judges decided in Decision Number 41/Pdt.G/2020/PN Sel , that the sale and purchase agreement for the disputed land object dated 5 June 2002 must be cancelled. Through this decision, the Panel of Judges provides legal protection through actual execution. The Defendants or parties who lose in the trial must return and hand over all the land that is the subject of the dispute to the Heirs (Plaintiffs). The land must be handed over in a vacant and free condition voluntarily.